Femoral cartilage defects initiate from medial meniscus extrusion or tibial cartilage lesions and expand in knee osteoarthritis as revealed by 3D MRI analysis - Katano, Hisako; Ozeki, Nobutake; Mizuno, Mitsuru; Endo, Kentaro; Koga, Hideyuki; Masumoto, Jun; Sekiya, Ichiro (Scientific reports, 2024)
Knee osteoarthritis is characterized by articular cartilage wear, with its morphological progression not fully understood. This study aimed to elucidate factors contributing to femoral cartilage defects and their expansion in medial knee osteoarthritis, using a novel approach analyzing cross-sectional MRI data arranged by disease severity. From a cohort of 277 women in the Kanagawa Knee Study, we selected 17 knees that showed a cartilage area ratio < 0.99 in the posteromedial femoral cartilage region as the subjects for this study. The morphological relationships between femoral cartilage defects and menisci, as well as between femoral cartilage defects and tibial cartilage lesions, were investigated. Among subjects aged 30 to 79 years, the proportion was significantly higher in the 70–79 age group. In 11 cases, the outer edge of the cartilage defect was observed to coincide with the inner edge of the medial meniscus. Tibial cartilage lesions corresponded to femoral cartilage defects in 15 cases. Our 3D MRI analysis demonstrated that femoral cartilage defects were initially caused by either medial meniscus extrusion or kissing tibial cartilage lesions, with subsequent expansion of these defects resulting from the combined effects of ongoing medial meniscus extrusion and progressive tibial cartilage degeneration. Trial registration: UMIN, UMIN000032826; September 1, 2018.